Accelerating the Generalized Born with Molecular Volume and Solvent Accessible Surface Area Implicit Solvent Model Using Graphics Processing Units. Issue 8 (24th December 2019) - Gong, Xiping; Chiricotto, Mara; Liu, Xiaorong; Nordquist, Erik; Feig, Michael; Brooks, Charles L.; Chen, Jianhan
Abstract : The generalized Born with molecular volume and solvent accessible surface area (GBMV2/SA) implicit solvent model provides an accurate description of molecular volume and has the potential to accurately describe the conformational equilibria of structured and disordered proteins. However, its broader application has been limited by the computational cost and poor scaling in parallel computing. Here, we report an efficient implementation of both the electrostatic and nonpolar components of GBMV2/SA on graphics processing unit (GPU) within the CHARMM/OpenMM module. The GPU‐GBMV2/SA is numerically equivalent to the original CPU‐GBMV2/SA. The GPU acceleration offers ~60‐ to 70‐fold speedup on a single NVIDIA TITAN X (Pascal) graphics card for molecular dynamic simulations of both folded and unstructured proteins of various sizes. The current implementation can be further optimized to achieve even greater acceleration with minimal reduction on the numerical accuracy. The successful development of GPU‐GBMV2/SA greatly facilitates its application to biomolecular simulations and paves the way for further development of the implicit solvent methodology. © 2019 Wiley Periodicals, Inc. Abstract : Implicit solvent arguably provides an optimal balance between efficiency and accuracy for simulating large‐scale conformational transitions of biomolecules. A graphics processing unit (GPU)‐accelerated implicit solvent model, generalized Born with molecular volume and solvent accessible surface area (GBMV2/SA), has been implemented in CHARMM/OpenMM program, offering ~60‐ to 70‐fold speedup on a single GPU. The GPU‐GBMV2/SA will greatly facilitate its application to biomolecular simulations in general.